Strategi Mengurangi Produk Defect pada Proses Pencetakan Documents Security dengan Penerapan Six Sigma di PT WCD - Sulistiani, Wiwin; Wahyudin, Wahyudin; Fasa, Nadia; Desinta, Mia (Fakultas Teknik Universitas Tulang Bawang, 2026)
PT WCD is a manufacturing company that operates in the Integrated Security Printing and System industry, producing Documents Security as its main product. In the production process, the company still faces several issues related to defective products, which affect production efficiency, quality costs, and customer satisfaction. This study aims to determine the main causes of defects in the Documents Security printing process and to provide suitable improvement suggestions. The method used in this research is Six Sigma with the DMAIC (Define, Measure, Analyze, Improve, Control) stages. Production data and the number of defective products during 2024 were analyzed using several statistical tools, including P-Chart, Pareto Diagram, and Fishbone Diagram. The results show that the most common defects are blobor, stains, and miss register. Based on the data analysis, the average DPMO value is 71,064 with a sigma level of 2.92, which indicates that the current process performance is still below the expected quality standard. Improvement proposals are prepared based on root cause analysis using the 5W + 1H method, along with the implementation of control plans and the use of batch cards to monitor production quality. The use of the DMAIC method in this research proves to be effective in identifying the key factors causing defects and reducing the defect rate, while also helping to improve the efficiency of the production process at PT WCD. Keywords : DMAIC, Defect, Document Security, Six Sigma.